83 Investigation Of Angiogenesis Associated Genes With Achilles Tendinopathy. (5th September 2014) - Rahim, Masouda; Posthumus, Michael; Collins, Malcolm; September, Alison V
Abstract : Introduction: Genetic factors have been implicated with risk of Achilles tendinopathy. Angiogenesis plays an important role in extracellular matrix (ECM) remodelling following mechanical loading. It is proposed that dysregulation of this process may alter the mechanical properties of the tissue thereby increasing the risk of injury. Furthermore, increased levels of angiogenic cytokines and growth factors have been reported in injured Achilles tendons [Pufe, 2001] and after cyclic stretching of tendon fibroblasts [Petersen, 2004]. Vascular endothelial growth factor (VEGF) is a potent pro-angiogenic factor and the biological effects of VEGF are mediated through its receptor kinase insert-domain receptor (KDR). Recently, polymorphisms within the VEGFA and KDR genes were found to be associated with risk of anterior cruciate ligament (ACL) ruptures [Rahim, 2014]. Thus, the aim of this study was to investigate if genes encoding proteins involved in angiogenesis-associated signalling are associated with risk of Achilles tendon injuries. Methods: A genetic-association study was conducted on 120 control participants (CON), 91 participants with Achilles tendinopathy (TEN) and 44 participants with partial or complete ruptures of the Achilles tendon (RUP). All participants were genotyped for the functional VEGFA rs699947, VEGFA rs1570360, VEGFA rs2010963, KDR rs2071559 and KDR rs1870377 polymorphisms. Haplotypes were also inferred for VEGFA and KDR . Statistical analyses were conducted to determine any significant differences (p < 0.05) between the groups (CON vs. TEN and CON vs. RUP). Results: No independent significant differences were observed in the genotype frequency distributions of any of the polymorphisms between the CON vs. TEN groups. However, there was a trend towards significance (p = 0.053) in the genotype frequencies for the VEGFA rs699947 polymorphism when comparing the CON group vs. the RUP group. The CC genotype was significantly over-represented (p = 0.019) in the CON group (24%) compared to the RUP group (3%). Inferred haplotype analyses showed no significant difference in the frequency distributions of the VEGFA or KDR haplotype combinations between the CON vs. TEN groups or the CON vs. RUP groups. Discussion: This pilot study did not find a statistical association with any of the five tested polymorphisms within the VEGFA and KDR genes using the Achilles tendinopathy risk model. However, the preliminary results are suggesting that the VEGFA rs699947 polymorphism may be implicated in acute injuries as noted in the Achilles tendon rupture cases. This hypothesis would be in alignment with the previous ACL risk model observations [Rahim, 2014]. These loci therefore need further interrogation in larger sample sizes. Studies are underway to explore the five polymorphisms within two independent case-control samples sets, in order to elucidate the potential biological significance of the angiogenesis-associated cell signalling pathway in the aetiology of Achilles tendon injuries (overuse and acute). References: Petersen et al . J Orthop Res. 2004;22:847–853 Pufe et al . Virchows Arch. 2001;439(4):579–585 Rahim et al . J Orthop Res. 2014 (in press)